KEEFEKTIFAN CAMPURAN MAHKOTA DEWA, JINTEN HITAM DAN KUNYIT PUTIH PADA HIPERTENSI (DI DUSUN PANDANSARI KEC. PURWOASRI KAB. KEDIRI TAHUN 2010) - Suryono, Suryono (Jurnal AKP, 2012)
Hypertension is a condition in which blood pressure is persistently its systolic above 140 mmHg, diastole above 90 mmHg. In certain stages of hypertension can cause complications such as stroke, myocardial infarction, chronic kidney disease and ensepalopati. The purpose of this study is to determine the effectiveness of mixed Mahkota Dewa, Jinten hitam  and kunyit putih on hypertension.The research design used in this research is pre experimental  a group with pre and post treatment approaches. The population was all patients with hypertension in the sub village of Pandansari  district of Purwoasri, research sample was part of hypertension patients in sub-village of Pandansari, district of Purwoasri Kediri  regency amount to 15 people. Analysis of data with  t- test with two paired sample  was conducted by comparing blood pressure before and after treatment, that  analyzed inferential were processed with SPSS software 14 to determine  the average and standard defiasi.The result show that the respondents consisted of 15 people there is a decrease of blood pressure systole levels of 151,33 mmHg to 134 mmHg, blood pressure diastole levels of 90,33mmHg to 82,67 mmHg in other word the blood pressure systole levels decreased by 11,5 % and blood pressure diastole 8,5 %.From the above results it is recommended that consumption of a mixture of Mahkota dewa, Jinten hitam and kunyit putih beneficial to decrease blood pressure in hypertension patients.